Fatty acids from soybeans: compatibility with Panonychus citri (Acari: Tetranychidae) and its two predators☆ - Qayyoum Muhammad Asif; Khan Bilal Saeed; Song Zi-Wei; Yi Tian-Ci; Inayat Rehan; Akram Muhammad Irfan; Mobarak Syed Husne; Li Dun-Song (Oilseeds and fats, crops and lipids)
Soybean oil is a significant alternative to synthetic chemicals for environmentally friendly and sustainable pest control. This study evaluated soybean oil and its fatty acids (palmitic, oleic, and stearic acids; individually) for their acaricidal and repellent effects against Panonychus citri (Tetranychidae) and its predators [Neoseiulus californicus and Neoseiulus barkeri [Phytoseiidae]) using laboratory foliar dipping and topical spray methods. The LC50 (Lethal Concentration) values for palmitic, oleic, stearic acids, and soybean oil against P. citri were 0.86%, 0.95%, 0.56%, and 0.05% for LDM (Leaf-dipping Method) and 11.92%, 5.34%, 1.46%, and 0.07% for TSM (Topical Spray Method). Soybean oil has maximum attraction (46.67 ± 3.6%) and significantly higher acaricidal effectiveness (46.25 ± 0.98%) compared to acids except oleic acid (50.83 ± 1.22%) against P. citri. Soybean oil showed the least toxicity, with the highest LT50 (Lethal Time) values for N. californicus (LDM: 1.19 h, TSM: 1.27 h). While soybean oil caused a less significant reduction in fertility and lower lethal efficacy (0.83 ± 0.83%) on predatory mites compared to P. citri. Compared to soybean oil, oleic acid reduces fertility rate (27 ± 1.60%) and is an effective repellent (65-75%) against N. californicus and N. barkeri and reduces prey consumption (15-16%) and laying eggs (0.75 ± 0.47) on treated surfaces compared to other treatments. Palmitic acid increases prey consumption (27.5 ± 3.28%) and fertility rates (5.00 ± 0.71) of N. californicus. Palmitic acid, despite being less toxic to P. citri, effectively repels predators, while soybean oil and oleic acid have stronger repellent effects. Leaf dipping was less effective than topical spray. Soybean oil, with its lower mortality rates and sublethal effects on reproduction and behavior, is a strong candidate for integrated pest management strategies. Oleic and palmitic acids, though effective, have repellency to beneficial predators.